Staging Images of Everyday Life in Late Colonial Korea: Colonial Visuality and the Proliferation of Amateur Photography. Issue 3 (3rd July 2021) - Kim, Michael
ABSTRACT: At the height of World War II, the Government General of Korea exerted considerable effort to propagandise and mobilise the colonial population. Films, fictional works, theatrical productions, posters and exhibits exhorted colonised Koreans to support the war effort and sacrifice themselves for the Japanese empire. At the same time, a considerable number of images from the period provided views of a more mundane everyday life, filled with smiling children going to school and farmers living an idyllic communal life. Late colonial publications offer a fascinating visual archive of Korea, and behind the plethora of everyday images was the spread of amateur photography. The Japanese colonial state in Korea systematically and purposefully used amateur photographs to visually "stage" everyday life, transforming the images into symbolic representations that legitimated colonisation. In terms of visual politics and the aims of this special issue, the study of the visual practices of the colonial period underscores how their influence has persisted long after liberation in 1945 and continues to affect representations of Korean society, culture and nationhood even today.